Long-term Follow-up of High Myopic Foveoschisis: Natural Course and Surgical Outcome - Gaucher, David; Haouchine, Belkacem; Tadayoni, Ramin; Massin, Pascale; Erginay, Ali; Benhamou, Nathanael; Gaudric, Alain (American journal of ophthalmology, 2007)
To determine the natural evolution and surgical indications of myopic foveoschisis (MF), which are still poorly documented, and the factors that predict poor prognosis. Retrospective observational case series. Twenty-nine operated and nonoperated cases of MF (29 eyes of 23 patients) were studied. All eyes underwent repeated examinations, including optical coherence tomographic (OCT) recordings, during a mean follow-up of 31.2 months. Special attention was paid to the evolution of visual acuity (VA) and to the thickness of foveoschisis. Mean refraction was −14.4 diopters, and mean axial length was 29.1 mm. OCT scans revealed that the foveoschisis was associated with macular anomalies: a premacular structure in 13 (44.8%) of 29 eyes, a foveal detachment in 10 (34.5%) of 29 eyes, and a lamellar macular hole in six (20.7%) of 29 eyes. Isolated foveoschisis was found in four eyes (13.8%). During follow-up, foveoschisis and VA worsened in 20 eyes and remained stable in nine. Ten of the 20 eyes that worsened had a premacular structure. A macular hole occurred in nine eyes, six of which had previously exhibited foveal detachment. Eleven eyes with foveoschisis underwent surgery, which improved VA significantly ( P = .04, Wilcoxon test), but three eyes developed a macular hole. MF may remain stable for many years without affecting VA. However, when it is combined with the presence of a premacular structure, the risk of a decrease in VA increases. When it is combined with foveal detachment, a macular hole seems to develop frequently, whether or not surgery is performed.